Levetiracetam versus phenytoin in children with status epilepticus - Gowhar Wani (Journal of Family Medicine and Primary Care, 2019)
Background: To compare the efficacy and safety of intravenous levetiracetam and phenytoin in status epilepticus. Methodology: A prospective, randomized controlled, nonblinded study was conducted in children 1 month to 12 years of age with active seizure and with status epilepticus. A total of 104 children were randomly allocated to either group 1 (levetiracetam) or group 2 (phenytoin) on the basis of computer-generated random number table. Children already on antiepileptic drugs, very sick children with shock, impending respiratory failure, or head injury, and children hypersensitive to phenytoin or levetiracetam were excluded. Data analysis was done by IBM SPSS statistics. Results: The mean age was 4.09 years with a male preponderance with the most common type of seizure being generalized type (74%). The seizures were controlled in all 104 patients initially within 40 min. Seizure control for 24 h was significantly better in group 1 (96%) when compared with group 2 (59.6%) (P = 0.0001). Minibolus of drug was given in 28.8% in group 1 and 46.2% in group 2 (P = 0.068).The seizure recurrence in groups 1 and 2 in the first hour was 1.9% and 5.8%, respectively (P = 0.61), whereas the recurrence between 1 and 24 h was significantly more in group 1 (34.6%) when compared with group 2 (3.8%) (P = 0.0001). The mean time to control seizure was comparable between both the groups (P = 0.71). There was no significant adverse effect in both the groups. Conclusion: Levetiracetam is more effective than phenytoin for seizure control for 24 h in children with status epilepticus, and it is safe and effective as a second-line therapy.